The effective ingredients of social support at home for people with dementia: a literature review. Issue 2 (18th April 2017) - Argyle, Elaine; Kelly, Tony; Gladman, John; Jones, Rob
Abstract : Purpose: Recent years have seen an increasing reliance on social support at home for people with dementia and the advocacy of a person centred and integrated approach in its provision. However, little is known about the effective ingredients of this support and how they differ from more generic or health-based services. The purpose of this paper is to explore the existing evidence base. Design/methodology/approach: A review of relevant literature was carried out, combining a systematic search and selection of articles with a narrative analysis. Findings: The review identified 14 relevant studies of varying research designs which yielded conflicting findings with regard to the optimal timing of interventions and their overall impact. This highlights the problems of review and generalisability when attempting to compare findings of research in this area. This was exacerbated by the blurred divide between health and social care and ambiguities in the meaning of the latter. Research limitations/implications: This methodological heterogeneity demonstrates the need for consistency in research approaches if comparisons are to be made. Further questions include the precise components that distinguish social care from health care, the optimal timing for the introduction of this care and whether adherence to good practice in this area can be linked to cost effectiveness. Originality/value: The review identifies relevant issues in need of further investigation and tentative themes emerging from the literature which suggest the utility of an adequately resourced, integrated and responsive approach to intervention.